Manajemen Integrasi Pembelajaran Bahasa Arab di Madrasah Berbasis Pondok Pesantren - Imam Makruf (IAIN Ponorogo, 2016)
Learning Arabic in madrasah nowadays is still yet to show optimal results. Madrasah which based on pesantren in Indonesia is very much. But it is not many that can produce graduates who speak Arabic well. Madrasah Aliyah Al-Mukmin in Sukoharjo is one of madrasah based on pesantren that has an integrative model of learning Arabic and shown to produce graduates who can speak Arabic well. This study focus to analyze the integration management model of learning Arabic. This studies was found that all subjects of religion and Arabic was developed in Arabic, from teaching materials, learning methods, and evaluation process. Arabic language is also used daily in the boarding which is supported by Arabic practical activities. The model is proven to improve all Arabic skills. Thus, this model worthy of adoption at the madrasah based on pesantren for learning Arabic. تعليم اللغة العربية فى المدارس الإسلامية الآن لما ينجع نجاحا تاما. المدارس المؤسسة على المعاهد الإسلامية كثيرة, ولكن قليلة منها الذي ناجح لتحصيل الخريجين الماهرين فى تكلم اللغة العربية. المدرسة العالية المؤمن بسوكاهرجوا من احدي المدارس التي تستخدم إدارة التعليم التكاملى و يستطيع الخريجون منها ان يتكلموا باللغة العربية تكلما جيدا. ويريد هذا البحث لتحليل الإدارة التكاملية فى التعليم اللغة العربية. ومن هذا البحث يعرف ان التعليم فى جميع المواد الدراسية الدينية واللغوية يقام باللغة العربية سواء كان فى كتابة المواد الدراسية و عملية التعليم و التقيم. وتكون اللغة العربية لغة اليومية فى المعهد المدرسي و فى متنوع العملية اللغوية فيه. فيستطيع هذه الإدارة التعليمية لترتقي مهارات اللغوية من التلاميذ. فلذلك من الممكن ان تستعمل هذه الإدارة لتعليم اللغة العربية فى المدارس الأخري المؤسسة على المعاهد الإسلامية.